UJI KADAR OKSIGEN PADA AIR MINUM KEMASAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHI KANDUNGAN OKSIGEN - Ayu Pertiwi; Imam Khambali; Rusmiati . (Poltekkes Kemenkes Surabaya, 2015)
Today, there are many oxygenated drinking water are sold in public. Information on labelsmentions that they contain oxygen of 20 ppm to 100 ppm. There are several factors affect oxygen level; hence, actual measurement of the oxygen content in oxygenated drinking water was carried out. The purpose of this study is to determine oxygen level in oxygenated drinking water and determine factors that affect oxygen content. This is a descriptive research. Data collection was carried out by measuring oxygen content in oxygenated drinking water. Samples was taken from pharmacy and super market atSurabaya, with four brands and by three repetitions. Data were then analyzed in by description. Test results of oxygen content in oxygenated drinking water on sample A showing thatthe original oxygen content is 5.26%, oxygen content of sample B was 13.78%, sample C was 3.62%, and sample D was 16.74%. The four sample show that the oxygen content is lower thanlabel statement. Oxygen reduction in oxygenated water is influenced by several factors including temperature of storage. Producers are suggested to improve control quality of their products and government should supervise oxygenated drinking water to avoid public deception because information mentioned does not match reality.